Clivagem e construções similares sob a perspectiva da gramática discursivo-funcional - Pezatti, Erotilde Goreti [UNESP] (My University, 2013)
This paper deals with so called cleft constructions and other similar structures in eight Portuguese varieties, aiming to show that the formal differences correspond to different functional strategies used by the Speaker to achieve his communicative intentions, in accordance with the theory of Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008). This study takes as evidence real spoken occurrences extracted from a corpus organized by the Linguistic Centre at the University of Lisbon. The results show the following distribution: cleft construction is a strategy for the pragmatic function Contrast marking; Focus-ser constructions are used to highlight a constituent and (é) que is used as an operator of emphasis which shows the speaker’s wish to intensify certain pieces of information.

Este estudo trata de estruturas denominadas clivagem ou construções -(é) que, nas variedades portuguesas, objetivando mostrar que as diferenças formais correspondem a diferentes estratégias utilizadas pelo Falante para atingir seus objetivos comunicativos, conforme preconiza a teoria da Gramática Discursivo-Funcional (HENGEVELD; MACKENZIE, 2008). Como material, utiliza ocorrências reais de uso extraídas do corpus oral organizado pelo Centro de Linguística da Universidade de Lisboa. A análise dos dados lusófonos revela que clivagem constitui uma estratégia de marcação da função pragmática Contraste; construções de Foco-Ser, por outro lado, são usadas para focalizar um constituinte, ou seja, marcam a função pragmática Foco; (é) que, por sua vez, funciona como um operador de Ênfase, já que assinala o desejo do Falante de intensificar uma parte de informação.
Cleft constructions and similar structures in the functional discourse grammar
Keywords: lusofonia; clivagem; foco; contraste; ênfase; lusophony; cleft constructions; focus; contrast; emphasis